Does Herding Behavior Exist in the Mongolian Stock Market? - Espinosa-Mendez, C (Elsevier B.V., 2020)
This investigation is among the first to examine the presence of herd behavior in the Mongolian stock market. Herding behavior was analyzed for the full sample data (1999 to 2019) including during bull and bear market periods, as well as high and low volatility states of markets. Additionally, the impact of four important events which occurred during these period were also tested: the establishment of the Finance Regulatory Committee of Mongolia (FRCM), the Global Financial Crises, Mongolia s inclusion in the FTSE Russell Watch list and economic boom in 2011. Using a cross-sectional absolute deviation (CSAD) model evidence of herding behavior was found in all the situations. © 2020